2020
DOI: 10.1002/ncp.10473
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Response Meta‐Analysis of the Impact of Body Mass Index on Mortality in the Intensive Care Unit

Abstract: Introduction: Both low and high body mass index (BMI) are associated with mortality in the intensive care unit (ICU). Although many studies have been done to determine the relationship between BMI and risk of mortality in the ICU, their results were inconsistent. This study aimed to conduct a dose-response meta-analysis of published observational studies to assess the effect of BMI on the risk of mortality in patients admitted to the ICU. Methods: PubMed, Scopus, and Google Scholar were searched to identify ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
5
1
1
Order By: Relevance
“…In earlier studies, even after adjusting for significant comorbidities, low weight showed an association with mortality [ 13 , 14 , 15 , 16 ]. However, in the current study, obese and overweight patients showed no protective factors, despite findings on previous research [ 17 , 18 , 19 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In earlier studies, even after adjusting for significant comorbidities, low weight showed an association with mortality [ 13 , 14 , 15 , 16 ]. However, in the current study, obese and overweight patients showed no protective factors, despite findings on previous research [ 17 , 18 , 19 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies are implemented on larger populations, with different subgroups, and have considered the etiological context (20,23). A recent dose-response meta-analysis on the effect of BMI on the mortality of ICUadmitted patients showed that for each unit of increase in BMI, a 0.6% decrease in mortality rate is expected (24). This study also discussed that while a BMI > 35 is a high risk feature in ICU-admitted patients, a BMI < 35 can play a protective role against mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies are intended to evaluate the issue in larger study populations, among different subgroups, and according to the etiology context [26,29,30]. A recent dose-response meta-analysis regarding the effect of BMI on the mortality of ICU-admitted patients showed that for each unit of increase in BMI (kg/m2), a 0.6% decrease in mortality rate is expected [31]. This study also discussed that while a BMI > 35 is a dangerous feature in ICUadmitted patients, a BMI < 35 can play a protective role against mortality.…”
Section: Discussionmentioning
confidence: 99%